Cortical activation changes in supratentorial stroke patients during posture-cognition dual task - He, Jun; Gong, Chen; Zhu, Xiang; Zhu, Shizhe; Geng, Ayan; Kan, Chaojie; Xu, Sheng; Wang, Tong; Guo, Chuan; Zhu, Lan; Wang, Qinglei (Frontiers in Neurology, 2025)
ObjectiveTo explore the effects of postural control and cognition interference on cortical activation during balance tasks in stroke patients.MethodsfNIRS was used to measure cortical activation in the SMC, PMC, and PFC in 30 subjects with supratentorial stroke while performing a postural single task (PST), cognitive single task (CST), and postural-cognitive dual task (DT). Differences in activation and correlations with patient balance or cognitive performance were analyzed.ResultsCST induced a higher level of activation in the unaffected SMC and bilateral PMC compared to PST. While DT resulted in more activation of the bilateral SMC and bilateral PMC compared to PST. No difference was found between DT and CST. Correlation analysis showed that activation of ROIs during balance tasks showed a positive correlation with the balance ability and cognitive performance of subjects.ConclusionBoth postural control and cognitive interference led to cortical activation changes during the tasks. Cognitive load was more likely to elicit greater cortical activation and approach the activation ceiling. These activations were intimately related to the patient’s ability to balance and cognitive performance. Subjects with better balance have a greater reserve of resources to allocate, enabling them to cope with tasks and improve task performance.Clinical trial registrationClinicalTrials.gov. Identifier ChiCTR2300077916.